Polycystic Ovary Syndrome in Adolescence: Challenges in Diagnosis and Management - Mariana Enxuto Santos Manique (2021)
Diagnosing polycystic ovary syndrome during adolescence is challenging since normal pubertal development overlap typical features of this syndrome. Therefore, several attempts have been made and expert consensus have been established aimed at standardizing specific adolescent criteria. Current recommendations reinforce the importance of balancing under and overdiagnosis. Under-diagnosing may compromise the prevention of future complications. However, over-diagnosis may have a clear negative impact both on physical and psychological health of the adolescent. Consequently, experts consider starting treatment targeted at the manifestations and/or comorbidities presented, even in the absence of a definite diagnosis whilst careful monitoring within the interim is granted. There is no approved treatment for this condition. Usually interventions start with lifestyle modifications to prevent excessive weight gain. Pharmacological agents such as combined oral contraceptives, metformin and antiandrogens may be used as adjuvants for symptomatic management. Nevertheless, there is insufficient evidence concerning its effects and safety within the adolescent population.